Comparative transcriptome and metabolome analysis suggests bottlenecks that limit seed and oil yields in transgenic Camelina sativa expressing diacylglycerol acyltransferase 1 and glycerol-3-phosphate dehydrogenase - Hesham M. Abdullah; Sudesh Chhikara; Parisa Akbari; Danny J. Schnell; Ashwani Pareek; Om Parkash Dhankher (Biotechnology for Biofuels, 2018)
Abstract Background Camelina sativa has attracted much interest as alternative renewable resources for biodiesel, other oil-based industrial products and a source for edible oils. Its unique oil attributes attract research to engineering new varieties of improved oil quantity and quality. The overexpression of enzymes catalyzing the synthesis of the glycerol backbone and the sequential conjugation of fatty acids into this backbone is a promising approach for increasing the levels of triacylglycerol (TAG). In a previous study, we co-expressed the diacylglycerol acyltransferase (DGAT1) and glycerol-3-phosphate dehydrogenase (GPD1), involved in TAG metabolism, in Camelina seeds. Transgenic plants exhibited a higher-percentage seed oil content, a greater seed mass, and overall improved seed and oil yields relative to wild-type plants. To further increase seed oil content in Camelina, we utilized metabolite profiling, in conjunction with transcriptome profiling during seed development to examine potential rate-limiting step(s) in the production of building blocks for TAG biosynthesis. Results Transcriptomic analysis revealed approximately 2518 and 3136 transcripts differentially regulated at significant levels in DGAT1 and GPD1 transgenics, respectively. These transcripts were found to be involved in various functional categories, including alternative metabolic routes in fatty acid synthesis, TAG assembly, and TAG degradation. We quantified the relative contents of over 240 metabolites. Our results indicate major metabolic switches in transgenic seeds associated with significant changes in the levels of glycerolipids, amino acids, sugars, and organic acids, especially the TCA cycle and glycolysis intermediates. Conclusions From the transcriptomic and metabolomic analysis of DGAT1, GPD1 and DGAT1 + GPD1 expressing lines of C. sativa, we conclude that TAG production is limited by (1) utilization of fixed carbon from the source tissues supported by the increase in glycolysis pathway metabolites and decreased transcripts levels of transcription factors controlling fatty acids synthesis; (2) TAG accumulation is limited by the activity of lipases/hydrolases that hydrolyze TAG pool supported by the increase in free fatty acids and monoacylglycerols. This comparative transcriptomics and metabolomics approach is useful in understanding the regulation of TAG biosynthesis, identifying bottlenecks, and the corresponding genes controlling these pathways identified as limitations, for generating Camelina varieties with improved seed and oil yields.